Tribological properties of BixTiyOz films grown via RF sputtering on 316L steel substrates (2015)
In this paper, we present the results obtained in surface chemical analysis, morphological characterization and evaluation of tribological properties of coatings of amorphous bismuth titanate (BixTiyOz) deposited on substrates made of 316L stainless steel using rf sputtering technique. The chemical elemental analysis was performed using Auger electron spectroscopy (AES), the morphology of the coatings was determined by atomic force microscopy (AFM). Measures of friction coefficient and wear rate were obtained by ball on disc test. EEA analyses allowed to establish that the first 10 nm of the coatings are comprised probably of Bi4Ti3O12 and Ti2O3, AFM measurements indicate that the coatings have an average roughness of 22.28nm and grain size of 50nm. Finally, the tribological tests established that the coefficient of friction and wear rate of the coated steel has similar values to the bare steel.